(untitled) (Anuário Antropológico, 2024)
Traditional medicine and ancestral knowledge are a fundamental part of the identity of indigenous communities, as they are the representation of their worldview on a physical and applied level; this knowledge has given them worldwide recognition due to the interest generated by the application of their procedures and their scientific support, which is why the international and intellectual property protection that has been given to this knowledge continues in development, and must face the new challenges that arise from the perspective of bioethics, considering in a relevant way the medical and the cultural sense that this topic implies. Currently, the Andean Community and multiple international organizations have addressed this issue, generating important legal debates, which will be treated in this article based on historical recognition, the situation of vulnerability and the challenges faced by indigenous communities for the protection of traditional medicine, proposing parameters to guarantee the preservation of traditional knowledge; the methodology used is a qualitative approach based on the study of jurisprudence and related doctrine.